Impact performances of steel tube-confined recycled aggregate concrete (STCRAC) after exposure to elevated temperatures. (February 2018) - Li, Wengui; Luo, Zhiyu; Wu, Chengqing; Duan, Wen Hui
Abstract: The impact behaviours of steel tube-confined recycled aggregate concrete (STCRAC) following exposure to elevated temperatures of 20 °C, 200 °C, 500 °C and 700 °C were experimentally investigated using a 100 mm-diameter split Hopkinson pressure bar (SHPB). The recycled coarse aggregate (RCA) replacement ratios were set as 0, 50% and 100%. The effect of RCA replacement ratio and exposure temperature on the impact properties of STCRAC were analysed in terms of failure modes, stress-strain time history curve and dynamic increase factor (DIF). The results show that the fire-damaged STCRAC can maintain its integrity during impact load. However, there were evident degradations in the dynamic behaviour of STCRAC after exposure to high temperatures of 500 °C and 700 °C. The ultimate impact strength, impact secant modulus and residual impact strength of STCRAC obviously decreased because of the damage due to high temperature exposure. But the degradations of both the ultimate impact strength and impact secant modulus of STCRAC under impact loading were less severe than those under quasi-static loading. The remaining strength factor and the DIF tended to increase with the raise of the elevated temperatures. Overall, during the impact loading, the fire-deteriorated STCRAC exhibited excellent impact behaviour.